A systematic review of rodent control as part of infectious disease control programs - Zeppelini, Caio Graco; Callefe, João Luiz Revolta; Coelho, Rachel; Silveira, Martha Silvia Martínez; Khalil, Hussein; Belmain, Steven R.; Bertherat, Eric Gerard Georges; Begon, Michael; Costa, Federico (International journal of pest management, 2024)
We investigated the empirical evidence supporting chemical rodent control as a public health program via a systematic search of the scientific databases PubMed and Web of Science, searching with term-strings for the concepts: "rodent control" and "zoonotic disease." Retrieved results were screened by title and abstract to eliminate studies that (i) do not involve rodents, (ii) do not contain a zoonotic component, and (iii) involve rodents and zoonosis, but no rodent control. The remaining articles were read in full, eliminating studies that lack direct assessment of rodent control effects, with pre-/post-control measures of epidemiological outcomes. Overall, 957 entries were recovered, but only five passed all elimination criteria. Studies were concentrated in Iran, focusing on zoonotic cutaneous leishmaniasis control. The studies found significant effects on zoonotic incidence post-control, but achieved low scores in quality-of-report assessment. The effectiveness of chemical rodent control as a measure against a zoonotic disease is in its infancy, and more studies are necessary to allow an adequate assessment of the method. It is strongly recommended that future work in the subject should adopt standardized guidelines to report studies